Clinical study of ectopic pregnancy at tertiary care center in Haryana, India - Chaudhary, Sushila; Chauhan, Meenakshi B.; Gupta, Anjali; Dalal, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Ectopic pregnancy is a life threatening condition in the first trimester of pregnancy. Diagnosis can be done by clinical examination, serum β-HCG and ultrasonography. This retrospective study was done to know the incidence, risk factors, and management of ectopic pregnancy. Methods: It was a retrospective study conducted on 75 patients of ectopic pregnancy admitted at tertiary care hospital in Haryana from February-2017 to January-2019. Data collected from record room and analysis done. Results: Total deliveries were conducted were 5064. The incidence of ectopic pregnancy was 1.48%, majority of the women were in the age group of 21-30 (68%), multi-parous (77.32%). The most common risk factor was abortion 33.33%, f/b tubal ligation was 13.13%, medical management of ectopic pregnancy done in 30.66%, 8% were managed by laproscopically and 58.66% by laparotomy. Conclusions: Safe sexual practices can reduce pelvic infections and ectopic pregnancy incidences. Early diagnosis before tubal rupture can reduce morbidity and mortality in ectopic pregnancy.